PROBLEMS OF USING THE REQUIREMENTS OF PROFESSIONAL STANDARDS OF THE IT INDUSTRY IN UNIVERSITY EDUCATIONAL PROGRAMS - Abdiyev, К.С.; Zhassandykyzy, М.; Primbetova, Г.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
. This article examines the problem of reflecting the requirements of professional standards of the IT industry in the content of university educational programs. Training future IT specialists in accordance with the requirements of employers is an urgent task for universities in Kazakhstan due to the fact that the introduction of an independent qualification recognition system is expected. An analysis of the content of the programs included in the Register was carried out, as a result it was determined that a large number of developed programs have names that coincide with the names of the old specialties - Information systems, Computer technology and software engineering. The most frequently used professional standards in programs have been identified. The content of professional standards has also been studied, using the example of one of them to show the problems of using the requirements for knowledge and skills required to perform labor functions. The main problem of comparing the content of two documents is the lack of a unified methodological approach to their development. For example, disciplines with the same name may have different content. Another important problem is the lack of measurability properties in the formulation of requirements for knowledge, skills, abilities and personal competencies necessary to perform the labor functions of the professions described in the standards. There is also the problem of the formal use of the names of professional standards, without projecting their requirements into the learning outcomes of educational programs. The authors proposed approaches to solving these problems. A convenience sampling survey was conducted to explore the views of business representatives and university professors. Most representatives of the two stakeholders note the need for cooperation to solve problems of comparability of professional standards and educational programs.